TRADISI FIDA' DI MASYARAKAT JAWA DALAM PERSPEKTIF HADIS - Choirun Nisa', Ashif Az Zafi (IAIN Kediri, 2020)
AbstractToday’s Javanese society, especially in the socio-religious field, is experiencing quite rapid development. One of the characteristics is that there are several new traditions which are more dominant about Islam. Therefore, the level of curiosity of the Javanese people towards the religious sciences is also increasing. The various traditions that exist among the Javanese are closer to the hearts of the whole community because they are in accordance with the cultural understanding that has existed since ancient times namely the respect / glory to the events of birth, marriage, and death. One tradition that developed in Javanese society is the fida 'tradition. Fida Tradition 'is a tradition which contains a dzikir event together to atone for the sins of people who have died by reciting surah al-ikhlas 100,000 times or tahlil 70,000 times. This situation, raises the writer's curiosity that the fida 'tradition in Javanese society that connects dhohir and ghoib is a part of scientific effort. This research belongs to the category of field research and literature research, where the writer conducts interviews with the kyai and also the writer seeks various references from several books, theses, journals, or documents that have a similar theme to the problem under study. From this research, it can be concluded that the fida 'tradition that exists in Javanese society in the perspective of Islamic law is a suggestion in the Islamic religion and there are a number of corroborating propositions.Keywords: Fida tradition; javanese community; islamic law